THE DEVELOPMENT OF INNOVATIVE LEARNING MATERIAL WITH A PROJECT TO IMPROVE STUDENT'S CRITICAL THINKING SKILLS IN THE TEACHING OF REDOX TITRATION - Silalahi, Gielf Justin Salisia Silrumson; Situmorang, Manihar (Chimica Didactica Acta, 2024)
Self-directed learning has become popular in higher education worldwide in recent years. As a result, students may have difficulty understanding higher education standards. Therefore, innovative learning materials that are relevant and easy to understand by students and provide opportunities for developing student's character so that they are competent in developing their knowledge capacity independently through high-level thinking skills such as critical thinking. Through the research and development method using the ADDIE Model, teaching materials are created by integrating the PjBL learning model to measure product feasibility scores, students' critical thinking abilities, and know student responses and learning outcomes. Based on the validation results, the average value of the validation results obtained was 89% (valid). After testing the product, it was discovered that the student response was 87.68% (good), the average critical thinking ability score was 87.36, indicating an increase and the average learning outcomes obtained by students were from 56.80 to 87.38, indicating an increase. Overall, the integrated teaching materials for the PjBL learning model on Redox Titration material are suitable.